18F-THK5351 Positron Emission Tomography Imaging in Neurodegenerative Tauopathies - Ezura, Michinori; Kikuchi, Akio; Okamura, Nobuyuki; Ishiki, Aiko; Hasegawa, Takafumi; Harada, Ryuichi; Watanuki, Shoichi; Funaki, Yoshihito; Hiraoka, Kotaro; Baba, Toru; Sugeno, Naoto; Yoshida, Shun; et al. (Frontiers in Aging Neuroscience, 2021)
Introduction: We aimed to determine whether in vivo tau deposits and monoamine oxidase B (MAO-B) detection using 18F-THK5351 positron emission tomography (PET) can assist in the differential distribution in patients with corticobasal syndrome (CBS), progressive supranuclear palsy (PSP), and Alzheimer’s disease (AD) and whether 18F-THK5351 retention of lesion sites in CBS and PSP can correlate with clinical parameters. Methods:18F-THK5351 PET was performed in 35 participants, including 7, 9, and 10 patients with CBS, PSP, and AD, respectively, and 9 age-matched normal controls. In CBS and PSP, cognitive and motor functions were assessed using the Montreal Cognitive Assessment, Addenbrooke’s Cognitive Examination–Revised, and Frontal Assessment Battery, Unified Parkinson’s Disease Rating Scale Motor Score, and PSP Rating Scale. Results:18F-THK5351 retention was observed in sites susceptible to disease-related pathologies in CBS, PSP, and AD. 18F-THK5351 uptake in the precentral gyrus clearly differentiated patients with CBS from those with PSP and AD. Furthermore, 18F-THK5351 uptake in the inferior temporal gyrus clearly differentiated patients with AD from those with CBS and PSP. Regional 18F-THK5351 retention was associated with the cognitive function in CBS and PSP. Conclusion: Measurement of the tau deposits and MAO-B density in the brain using 18F-THK5351 may be helpful for the differential diagnosis of tauopathies and for understanding disease stages.